Renewing Royal Imagery : Akhenaten and Family in the Amarna Tombs - David, Arlette, (Harvard Egyptological Studies ;, 2021)
In Renewing Royal Imagery: Akhenaten and Family in the Amarna Tombs , Arlette David offers a systematic, in-depth analysis of the visual presentation of ancient Egyptian kingship during Akhenaten's reign (circa 1350 B.C.) in the elite tombs of his new capital, domain of his god Aten, and attempts to answer two basic questions: how can Amarna imagery look so blatantly Egyptian and yet be intrinsically different? And why did it need to be so?.